Physiological roles of parathyroid hormone-related protein - Lai, Ngan Kam; Martinez, Dorothy (Acta Biomedica Atenei Parmensis, 2019)
Background: Parathyroid hormone related peptide (PTHrP) is widely expressed in a variety of normal fetal and adult tissues. Aim of work: Review of these normal physiologic functions of PTHrP in each of these tissues. Method: Performed literature search on pubmed on articles related to PTHrP and physiologic roles. Results: PTHrP is expressed in wide range of sites in the body with roles including relaxation of vessels and smooth muscle cells, and regulation of development. PTHrP also mediates humoral hypercalcemia of malignancy. PTHrP can be falsely elevated in benign conditions. Lastly, PTHrP has a pharmacological role in osteoporosis treatment. Conclusions: PTHrP has many various physiological roles besides mediating humoral hypercalcemia of malignancy. (www.actabiomedica.it)